Bite-sized marketing realistic solutions for the overworked librarian - Dowd, Nancy, 1956-; Evangeliste, Mary.; Silberman, Jonathan, 1982-; ebrary, Inc. (Chicago : American Library Association, 2010)
Filled with contemporary marketing ideas, and structured to quickly impart simple and cost-effective ideas for marketing your library.
Word-of-mouth marketing -- Bring your library to life with a story -- How to market electronic resources -- Public relations 101 -- Outreach -- Advocacy -- The new marketing tools -- Design -- Branding -- Marketing best practices.
Includes index.
Electronic reproduction.
Keywords: Libraries -- Marketing; Libraries -- Public relations; Electronic books